FENOMENA KELUHAN DALAM SERIAL TELEVISI “SHINYA SHOKUDO: TOKYO SERIES” : KAJIAN SOSIOPRAGMATIK - Frumentius Adrianus Arve; Anak Agung Ayu Dian Andriyani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
Social interaction constitutes a fundamental aspect of human life and serves as the primary medium through which communication among individuals is established. The aim of this study is to identify the forms of complaint speech acts in the television series Shinya Shokudo: Tokyo Series through a sociopragmatic approach. This research not only illustrates complaints occurring between sellers and buyers but also reflects the broader phenomenon of complaints within the everyday life of Japanese society. The data were obtained from ten episodes of the series, in which various complaint phenomena were observed. The study employed a qualitative descriptive method, utilizing observation and note-taking techniques, as well as pragmatic equivalence for data analysis. The findings reveal that complaint strategies are realized in direct, indirect, avoidance, and even threatening forms, selected in accordance with social relations, power distance, and interactional context. These findings emphasize that complaint speech acts serve dual functions: expressing dissatisfaction while simultaneously maintaining politeness and the cultural value of wa (harmony) in Japanese communication practices.